The Effect of Portland Cement on Fly Ash Bottom Ash Geopolymer Hybrid Concrete Exposed to Peat Water Environment - Monita Olivia; Rudy Satriya Pratama; Ferisma Ratu Giri; Iskandar Romey Sitompul; Alfian Kamaldi; Gunawan Wibisono; Edy Saputra (AMTS and Faculty of Engineering - Universitas Riau, 2022)
Geopolymer hybrid concrete is prepared by activating fly ash bottom ash with an alkaline solution and curing with Ordinary Portland Cement (OPC). OPC could be added to the mixture to increase the reaction, promote hydration, and assist in curing at room temperature. Peat water is an acidic organic environment that may reduce the durability of concrete. The purpose of this research is to determine the effect of Portland cement on the properties of FABA geopolymer hybrid concrete exposed to peat water. Portland cement was used in geopolymer as an additive and a substitute. Compressive strength, porosity, and weight change were evaluated for both mixtures. The NaOH molarities were 10, 12, and 14M, the NaOH/sodium silicate ratios were 1.5, 2.0, and 2.5, and the Ordinary Portland Cement percentages were 0, 10, and 15%. Specimens were exposed to peat water for up to 91 days following 28 days of room temperature curing. The geopolymer mixture with 10M NaOH, 2.5M Ms, and 15% OPC had the highest compressive strength and the lowest porosity. The FABA geopolymer hybrid with OPC had a slightly greater compressive strength and a lower porosity than the geopolymer containing OPC as a cement replacement material. In addition, weight change is more stable in geopolymers containing OPC. Based on the performance of both mixes in peat water, it is recommended to use OPC as an additive in FABA geopolymer hybrid concrete.